Pengujian Kualitas Sistem Informasi Kesehatan Periksa.ID Berbasis Autentikasi Menggunakan Software Testing Life Cycle - Salshabila, Andini Dwi; Sutanto, Imam; Hosizah, Hosizah; Pertiwi, Tria Saras (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The advancement of information technology in the healthcare sector encourages hospitals to implement reliable and secure digital systems, one of which is the Periksa.id application. This application is used by doctors to record inpatient examination results and is now equipped with a fingerprint authentication feature. This study aims to evaluate the quality of the Periksa.id application using the Software Testing Life Cycle (STLC) method, which consists of six stages: requirement analysis, test planning, test case design, test environment setup, test execution, and test closure. The research was conducted at Soeharto Heerdjan Hospital over a period of three months with a total of 200 virtual users involved in the reliability testing. Testing was carried out on both functional and non-functional aspects, including response time, reliability, security, portability, as well as positive and negative testing, using tools such as JMeter, WAPT, and ZAP. The results showed that the application met over 85% of the software quality criteria, although several minor bugs and 12 security vulnerabilities (2 high, 10 medium) were identified and require improvement. This study contributes to the evaluation of web-based hospital application systems to enhance the efficiency of medical services and ensure secure patient data management.